Inflammation and endothelial function‐related gene polymorphisms are associated with carotid atherosclerosis—A study of community population in Southwest China - Jing Lu; Wei Peng; Xingyang Yi; Daofeng Fan; Jie Li; Chun Wang; Hua Luo; Ming Yu (Brain and Behavior, 2023)
Abstract Objectives To investigate the relationships between 18 single nucleotide polymorphisms with carotid atherosclerosis and whether interactions among these genes were associated with an increased risk of carotid atherosclerosis. Methods Face‐to‐face surveys were conducted with individuals aged 40 or older in eight communities. A total of 2377 individuals were included in the study. Ultrasound was used to detect carotid atherosclerosis in the included population. 18 loci of 10 genes associated with inflammation and endothelial function were detected. Gene‐gene interactions were analyzed using generalized multifactor dimensionality reduction (GMDR). Results Among the 2377 subjects, 445 (18.7%) subjects had increased intima‐media thickness in the common carotid artery (CCA‐IMT), and 398 (16.7%) subjects were detected with vulnerable plaque. In addition, NOS2A rs2297518 polymorphism was associated with increased CCA‐IMT, IL1A rs1609682, and HABP2 rs7923349 polymorphisms were associated with vulnerable plaque. Besides, GMDR analysis showed significant gene‐gene interactions among TNFSF4 rs1234313, IL1A rs1609682, TLR4 rs1927911, ITGA2 rs1991013, NOS2A rs2297518, IL6R rs4845625, ITGA2 rs4865756, HABP2 rs7923349, NOS2A rs8081248, HABP2 rs932650. Conclusion The prevalences of increased CCA‐IMT and vulnerable plaque were high in Southwestern China's high‐risk stroke population. Furthermore, inflammation and endothelial function‐related gene polymorphisms were associated with carotid atherosclerosis.